ANALISIS PELAKSANAAN PROGRAM PENGELOLAAN TEKNOLOGI TEPAT GUNA (TTG) OLEH BADAN PEMBERDAYAAN MASYARAKAT DAN DESA (BAPERMADES) PROVINSI JAWA TENGAH - Audia Arsyad Nurwinendra; Hardi Warsono (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
This research was arranged to analyze the implementation of TTG managerial program from Bapermades of Central Java Province and the constraints that may affect the TTG’s program implementation. Bapermades of Central Java province has not implement guidance and facilitation of optimal thus giving rise to problems in implementation. This research is kind of descriptive- qualitative research where the data was collected through interviews, observation, and literature study. Informants were taken by author is the head of SDA and TTG sub division, TTG’s sub division staff, Posyantek officials, and representatives of community groups. The Author used the indicators of TTG’s program implementation guides from Minister of Home Affairs Regulation and Central Java Governor Regulation then it compared accordingly with problems in the field. Based on the research, the results obtained that needs mapping of TTG are still in manual. Socialization, information media, IT knowledge and training are still in deficiency. Posyantek formation is still uneven and regulatory in Regents Regulation level as well as a special institution for TTG has not yet been established. The Number of human resources and budget limitation is the kind of obstacles for conducting the program. Based on the results, this study concludes that the implementation of TTG managial program have conducted in accordingly with the applicable guidelines of regulation, but it still encountered some obstacles so it can’t be implemented to the fullest. The advice given by the author is this program needs to be socialized and assisted to the community,it needs to improve the information media, training and developing in the IT field as well as increasing the cooperation with various stakeholders.